Foundations of ancient Egyptian religion: Fear of death and/or pursuit of order - E. V. Alexandrova (Шаги, 2024)
The idea that fear of death forms the basic motivation for cultural and religious practices has gained attention of cognitive science and has been experimentally tested in recent decades. It is now known as the terror management theory (TMT). However, the idea itself was influential in scholarship at least since the 19th century and has had a significant impact on Egyptology throughout its history. In this article classical and modern works on ancient Egyptian religion and funeral practices are analyzed in order to highlight peculiarities of Egyptological reliance on the topos of fear of death. It can be noted that the use of the category of beneficiary for analysis of funerary literature and ritual is connected with the notion of benefit as a deliverance from fear of death. This perspective on benefits played its role in the formulation of the “democratization of the Afterlife” theory. The model centered on the idea of the orderliness of the world, proposed by J. Assmann, is considered as an alternative approach. It can be further developed in light of the compensatory control theory (CCT). Assmann limited himself to the study of religion as communication with gods. This paper explores funerary practices within the framework of ‘religion as propagation of Maat’. Finally, such specific traits of Egyptian funerary practices as threat-formulae, letters to the dead and heart amulets are analyzed as modes of execution of personal and compensatory control.